PENGEMBANGAN KEPUASAN KERJA KARYAWAN YANG DITINJAU DARI KEBIJAKAN KOMPENSASI DAN SISTEM PENGEMBANGAN KARIR - Misbachul Munir; Fayola Issalillah; Didit Darmawan; Ella Anastasya Sinambela; Rahayu Mardikaningsih (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The dynamics of HR management that continues to increase now should encourage management in every organization to change the pattern of HR management. Management needs to make efforts to maintain and improve their human resources. One of them is by creating employee job satisfaction. The purpose of this study is to determine the role of compensation and career development in employee job satisfaction. In this study, 46 respondents were used as a sample, which was carried out using the census technique. The analysis uses descriptive analysis and inferential analysis, multiple linear regression. The results show that employee job satisfaction is partially and simultaneously influenced by compensation and career development.